Fulfilling Both And Mind Obligations For Husbands Who Are Passing A Prison Criminal In Sidoarjo Community Institutions (Islamic Legal Analysis) - Widodo, Purwo (Journal of Social Science and Economics, 2023)
Everyone must have their own goals in life, one of which is to get married. And you need to know that humans have been prepared by Allah SWT for their own partners which has been written in Lauhul Mahfudz several years ago. Marriage can also make our hearts peaceful, calm and strong. when we can form a family that is sakinah mawaddah warohmah. Meanwhile, in marriage we must be prepared to be hit by various family problems. The word an-nikah means al-wath'u (coitus), namely, the relationship between husband and wife. Az-zawwaj according to fiqh terms, is a bond given by Allah which is useful for husband and wife to experience pleasure in the prescribed manner. Marriage is a social necessity in fostering life and the continuity of human existence. It is also an affair that is favored by the soul and a natural activity for all beings. Therefore, several tribes met each other. Built there families and nations. Seeing the problems in society, the researcher is very interested in conducting research for a small family that is unable to provide for itself physically and mentally because the husband who is responsible for the family goes to prison. The researcher also wants to explore in detail the economic impact on the family whose head of the household is left behind in a detention cell. There is a lot of news in the community that a family priest is serving a prison term, thinking that the family's life will be unstable and many problems will arise. From some of the explanations above, the researcher is curious about how the family's economy really is after the husband is imprisoned for a crime and applies this in the research title of fulfilling physical and spiritual obligations for the husband who is serving a prison sentence at the Sidoarjo correctional institution. The aim of this research is to determine the fulfillment of physical and spiritual obligations for husbands serving prison sentences at the Sidoarjo correctional institution and to determine the analysis of Islamic law regarding the fulfillment of physical and spiritual obligations for husbands serving prison sentences at the Sidoarjo correctional institution. The research method used is a qualitative case study approach. The results of this research are that a husband with convict status can still provide a living according to his ability. They earn a living from developing independence in prisons in collaboration with third parties. They receive wages for the work they do.